Study on the General Exceptions Provided By WTO in the Reference of Trade and Environmental Issues - Kavyanjali Tewari (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Article 20 in GATT 1994 is a general exception for members of WTO. In this exception the members are exempted from the rules. There are two general exceptions which is Article 20 (b) and Article 20 (g). They are for protecting environment as in article 20 (g) the natural resources that are exhaustible can be conserved and in article 20 ( b) it is given that any country can protect its animal, plant, human and health. This article is framed in such a manner that it protects the environment without restricting trade. There are nine disputes under WTO that are related with environment and from these six disputes are in GATT and remaining are under WTO. The present study will discuss all these disputes in the reference of trade and environmental issues. Many research is focusing on WTO because it is only one organization which settles the dispute of trade and environment but is this organization is sufficient is the matter of research. The present is study will discuss all disputes related with trade and environment.
Keywords: Uruguay Round; Environment; Multilateral Trading System; Sustainable development; UN; WTO